UPAYA PENINGKATAN KESEHATAN MELALUI PELATIHAN MASSAGE PEMUDA KARANG TARUNA DESA BOJONG KONENG - Sri Nuraini; Taufik Rihatno; Aan Wasan (SELEBRASI: Jurnal Pengabdian Masyarakat, 2023)
Community service activities will be attended by the people of Bojong Koneng Village, Babakan Madang District, Bogor - West Java. The objectives of this activity are: a) the general objective is an effort to maintain health through massage training for the people of Bojong Koneng Village, Babakan Madang District, Bogor - West Java in improving skills and maintaining the fitness and health of family members with massage, b) special objectives, These include: 1) introducing the importance of massage training, 2) improving the quality, 3) being able to apply their knowledge, skills and abilities, and massage skills to the community in the village of Bojong Koneng, especially to family members. This community service activity can be carried out well, because: 1) facility assistance in the form of rooms and supporting media for the delivery of materials that have been prepared by village officials, 2) facility assistance in the form of open spaces that have been prepared by the village for massage training and practice for the community. the community, 3) equipment assistance from the head of the training implementer for the implementation of the practice which was provided free of charge to each training participant in the form of a goodie bag containing: 1 large white towel, 1 small white towel, 1 botoh handbody, and 1 bottle of massage oil. , 4) the participants took every stage of the activity that was held from beginning to end in earnest, 5) the participants actively asked questions at every stage of practice that they did not understand, 6) the participants wanted to develop the skills they had acquired to be applied to family members with the aim of maintaining health and fitness.